Engagement of Na,K-ATPase β3 subunit by a specific mAb suppresses T and B lymphocyte activation - Chiampanichayakul S. (2014)
In order to identify new molecules involved in regulation of T cell proliferation, we generated various mAb by immunization of mice with the T cell line Molt4. We found one mAb (termed P-3E10) that down-regulated the in vitro T cell proliferation induced by CD3-specific OKT3 mAb. The P-3E10 mAb was also able to inhibit IFN-γ, IL-2, IL-4 and IL-10 production of OKT3-activated T cells. The antigen recognized by P-3E10 mAb is broadly expressed on all hematopoietic as well as on all non-hematopoietic cell lines tested so far. Within peripheral blood leukocytes, the P-3E10 antigen was detected on lymphocytes, monocytes and granulocytes. Human umbilical vein endothelial cells (HUVEC) also scored positively. By evaluating the effect of P-3E10 mAb on these cell types we found that it also inhibited anti-IgM-induced B cell proliferation. However, it did not block growth factor-mediated proliferation of HUVEC, and spontaneous proliferation of SupT-1, Jurkat, Molt4 and U937 cell lines. Moreover, it did not influence phagocytosis of human blood monocytes and granulocytes. Biochemical analysis revealed that the P-3E10 antigen is a protein with a mol. wt of 45-50 kDa under non-reducing and 50-55 kDa under reducing conditions. By using a retroviral cloning system, the P-3E10 antigen was cloned. Sequence analysis revealed the P-3E10 antigen to be identical to the β3 subunit of the Na,K-ATPase.